Employee Financing Diversity and Corporate Social Responsibility Impact on Sustain Competitive Advantages in Sustainable Firm Performance - Muhammad Naveed Jamil; Abdul Rasheed; Teguh Budiman; Mahmoona Mahmood (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study aims to examine the impact of Employee Financing Diversity and Corporate Social Responsibility on the firm performance. The study analyzes data from 300 Non- Financial Firms listed on the Pakistan Stock Exchange covering the period from 2011 to 2020, adding more literature in this field. The panel data methodology is used for estimation. Panel data includes a cross-sectional study with time series observation analysis. The empirical results indicate that Employee Financing Diversity and Corporate Social Responsibility enhance firm value, assets, growth, and profit and build firm trust and loyalty with the customer. The results showed that Tobin’s Q and ROA performance is more favorable and sustainable with Employee Financing Diversity and CSR model better and sustainable value produced within account base performance of ROA and ROE while firm size high significant and important all the time showing in all models. The recommendation and implication are clear that the role of Employee Financing Diversity and Corporate Social Responsibility are significant value in boosting the firm production and enhancing sustainable firm performance. It builds up the firm association with employees, customers, as well as investors.